(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Objective: Experimental gastric ulcer is known to cause systemic metabolic disturbances affecting distant organs, including the liver. This study aimed to evaluate the morphofunctional relationship between the activity of hepatic detoxification enzymes and the development of hepatocyte apoptosis in an experimental model of gastric ulcer.